Employee Performance Analysis: A Study At PT Panin Securities Semarang - Andrawati, Lisa; Sulistyorini, Sulistyorini (Economics and Business Solutions Journal, 2025)
This study aims to determine the effect of leadership style, organizational culture, and work motivation on the performance of Panin Securities employees. This type of research uses quantitative methods. The population determined in this study were employees at Panin Securities, totaling 35 people. In sampling, the technique used is to use saturated samples. Data was collected using questionnaires and then analyzed using multiple linear regression methods. The data was processed using SPSS (Statistical Program for Social Science) version 25 with a validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, regression analysis, hypothesis test, f test, and coefficient of determination. The results showed that leadership style has a significant positive effect on employee performance, organizational culture has a considerable positive impact on employee performance, and work motivation has a substantial positive effect on employee performance. Based on simultaneous tests, the variables of leadership style, organizational culture, and work motivation show working together influences overall employee performance. Companies must continuously evaluate and monitor to influence style leadership, culture, organization, and motivation. Work to performance employees. Through surveying employees, performance data analysis, and feedback sessions, the company can identify areas that need repair and implement appropriate corrective action
Keywords: Leadership Style; Organizational Culture; Work Motivation; Employee Performance